A novel model to eliminate the doubly near‐far problem in wireless powered communication network - Jitendra Singh; Akanksha Chaturvedi; Sandeep Sharma; Abhilash Singh (IET Communications, 2021)
Abstract In this paper, the newly emerging wireless powered communication network is studied. In doing so, the performance of the global controller (GC) is evaluated, which coordinates the wireless energy transmissions between two sensor nodes. Both the sensors have the same harvested energy for uplink (UL) transmission of information through time‐division‐multiple‐access. Afterwards, the information transmission time is optimised to maximise the common throughput of both the sensors with a total time constraint based on the user's UL channels along with the same harvested energy value. Further, due to the “doubly near‐far” phenomenon, a remote sensor from the GC, which has poor channel conditions than a nearer user, has to transmit more time in the UL for maximum common throughput. To overcome this problem, the energy exchange (EEx) model is proposed where both sensors first harvest the same amount of wireless energy and then exchange energy to nullify the different channel conditions between sensors and GC to send their independent information in the UL. Simulation results demonstrate the EEx Model's effectiveness over without energy exchange (WEEx) model in eliminating the doubly near‐far problem in wireless powered communication network but at the cost of maximum sum‐throughput. The maximum sum‐throughput of the proposed EEx model is 35% lower than the WEEx model. However, the average BER in the proposed EEx model is 74.6% lower than the WEEx model, which increases the reliability of the model.